2012
DOI: 10.1073/pnas.1208951109
|View full text |Cite
|
Sign up to set email alerts
|

Cultural transmission of social essentialism

Abstract: Social essentialism entails the belief that certain social categories (e.g., gender, race) mark fundamentally distinct kinds of people. Essentialist beliefs have pernicious consequences, supporting social stereotyping and contributing to prejudice. How does social essentialism develop? In the studies reported here, we tested the hypothesis that generic language facilitates the cultural transmission of social essentialism. Two studies found that hearing generic language about a novel social category diverse for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
421
6
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(460 citation statements)
references
References 44 publications
28
421
6
5
Order By: Relevance
“…Paired-sample t tests revealed that infants in the animate condition, like those in Experiment 1, looked significantly longer to inconsistent trials (56.5% of looking time) than to consistent trials [43.5%; t (23) = 2.87, P < 0.01; this difference was also reflected in a strong trend toward a main effect of trial type in the ANOVA, F (1,40) = 3.974, P = 0.053]. In contrast, for infants in the inanimate condition the difference between looking times to inconsistent (49.3%) and consistent trials (50.7%) was not statistically significant [t (23) = 0.33, P > 0.7; Fig. 2].…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Paired-sample t tests revealed that infants in the animate condition, like those in Experiment 1, looked significantly longer to inconsistent trials (56.5% of looking time) than to consistent trials [43.5%; t (23) = 2.87, P < 0.01; this difference was also reflected in a strong trend toward a main effect of trial type in the ANOVA, F (1,40) = 3.974, P = 0.053]. In contrast, for infants in the inanimate condition the difference between looking times to inconsistent (49.3%) and consistent trials (50.7%) was not statistically significant [t (23) = 0.33, P > 0.7; Fig. 2].…”
Section: Methodsmentioning
confidence: 88%
“…By the preschool years, parents and other adults have begun to instruct children in the conventional behavior of their own groups, and they talk about the behaviors of social groups in generic terms (22). Children may generalize from this input and come to expect that groups are likely to be characterized by particular behaviors and that adherence to those behaviors is normative (23). Children might also learn from interacting with others that conventional behaviors can be socially rewarding, correct, or useful.…”
mentioning
confidence: 99%
“…Rothbart and Taylor (1992) further suggested that essentialist thinking may affect perceptions of specific groups, and accentuate inter-group differences. The pervasive nature of essentialist thinking and the role of language in the cultural transmission of essentialist attributions (as outlined by Rhodes, Leslie, and Tworek, 2012) have implications for practitioners and administrators concerned about the potential for stereotyping and prejudice.…”
Section: Essentialist Beliefsmentioning
confidence: 99%
“…It is, however, conceivable that essentialist views of groups of children (or 'categories of special educational need') may, through adherence to prejudicial beliefs or assumptions, undermine teachers' preparedness to engage fully with inclusive education. In relation to teachers' beliefs in their efficacy (Jordan & Stanovich, 2004;TschannenMoran & Johnson, 2011) it is possible that beliefs in the essentialist characteristics of certain groups undermine teachers' beliefs that it is possible to support greater progress and/or achievement for children (Rhodes et al, 2012;Southerland et al, 2011).…”
Section: Essentialist Beliefsmentioning
confidence: 99%
“…For example, Rhodes et al (2012) introduced 4-year-old children to a new, made-up social category, called "Zarpies" via a series of statements that described specific individuals (e.g., "This is a Zarpie. This Zarpie loves to sing") or that made generic claims (e.g., "This is a Zarpie.…”
mentioning
confidence: 99%